CRY OF THE PHULAGURIANS : A DISCOURSE ON THE CAUSES BEHIND - Dr. Kamal Chandra Pathak, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The blood that shed on the soil of Phulaguri is a tragic history written on the unwritten hearts of the Phulagurians of erstwhile Nowgong district of Assam. Each and every revolution is born out of the womb of injustice and the revolt of Phulaguri is also cannot be spared of this. The peasants of Phulaguri had fiercely resisted against the colonial government and the evils of foreign rule resulted to the culmination of the natural anger emanated from hunger in the succeeding days. In colonial exploitation system, those who suffered at best at the hands of the British government were the peasants and the subaltern class and the revolt of the Phulagurians is a clear example to that. Through this paper an attempt has been made here to address all this.